Safety profiles of offspring born from early-follicular long-acting GnRH agonist protocol and daily mid-luteal GnRH agonist protocol: a retrospective study - Linqing Du; Jianyuan Song; Wenqian Fan; Tian Ye; Huijuan Kong (BMC, 2024)
Abstract Background The gonadotropin hormone-releasing hormone agonists (GnRH-a) have been widely used for controlled ovarian stimulation in assisted reproductive technology (ART). The early-follicular long-acting GnRH-a long protocol (EFL) and the luteal phase short-acting GnRH-a long protocol (LPS) are commonly used GnRH agonist protocols. We conducted a retrospective analysis to assess and compare the rates of congenital abnormalities and safety profiles in offspring born from the EFL and LPS protocols. Methods We conducted a retrospective cohort study to analyze and compare neonatal data from patients who using EFL or LPS protocols at our center between January 1, 2014, and June 30, 2017. The study ultimately included 1810 neonates from 1401 cycles using the EFL protocol and 2700 neonates from 2129 cycles using the LPS protocol.The main outcome measures are gestational age at delivery, birth weight, and congenital anomaly rate.To assess the influence of various factors on congenital abnormalities, a random-effects logistic regression model was employed. Results The EFL and LPS protocols led to similar congenital anomaly rates (1.64% vs. 2.35%, P = 0.149). No significant differences were found between the two groups regarding birth weight and its categories, newborn gender and congenital anomaly rate. The results of the multivariate logistic regression model indicated no association between congenital anomaly and BMI, duration of infertility, treatment protocol, fertilization method, or embryo transfer stage. Compared with singleton pregnancies, the probability of congenital defects in multiple pregnancies was 2.64 times higher (OR: 2.64, 95% CI: 1.72-4.05, P < 0.0001). Newborns with congenital defects were born with a lower gestational age compared with full-term pregnancies. Conclusion In conclusion, the EFL protocol is considered a safe option for ensuring offspring safety, comparable with the LPS protocol; however, multiple pregnancies represent an independent risk factor for congenital abnormalities. This approach can be widely adopted; however, prioritizing single embryo transfers is strongly recommended to minimize the potential risks associated with multiple pregnancies in offspring.